Fungal Grapevine Trunk Diseases in Romanian Vineyards in the Context of the International Situation - Maria-Doinița Muntean; Ana-Maria Drăgulinescu; Liliana Lucia Tomoiagă; Maria Comșa; Horia-Silviu Răcoare; Alexandra Doina Sîrbu; Veronica Sanda Chedea (Pathogens, 2022)
Vitis vinifera, known as the common grape vine, represents one of the most important fruit crops in the world. Romania is a wine-producing country with a rich and long tradition in viticulture. In the last decade, increasing reports of damage caused by grapevine trunk diseases (GTDs) have raised concerns in all wine producing countries. Up to now, no study was performed regarding the GTDs situation in Romania, an important grapevine grower in Europe. In this study, we aim, after a comprehensive presentation of the fungal GTDs worldwide, to review the scientific information related to these diseases in Romania in order to open a national platform in an international framework. In order to achieve this, we consulted over 500 references from different scientific databases and cited 309 of them. Our review concludes that, in Romania, there is little amount of available literature on this matter. Three out of six fungal GTDs are reported and well documented in all of the Romanian viticultural zones (except for viticultural zone 4). These are Eutypa dieback, Phomopsis dieback, and Esca disease. Of the fungal pathogens considered responsible Eutypa lata, Phomopsis viticola and Stereum hirsutum are the most studied and well documented in Romania. Management measures are quite limited, and they mostly include preventive measures to stop the GTDs spread and the removal of affected grapevines.